Insecticidal activity of Laurelia sempervirens (Ruiz & Pav.) Tul. essential oil against Sitophilus zeamais Motschulsky - Torres,Cristian (Instituto de Investigaciones Agropecuarias, INIA, 2014)
The maize weevil Sitophilus zeamais Motschulsky is a worldwide key pest of stored products. Usually contact insecticides or fumigants are used against it, but problems as toxic residues, human intoxications, and resistance have triggered the search for alternative control methods as the use of essential oils. The objective of this research was to assess under laboratory conditions, the insecticidal properties of Laurelia sempervirens (Ruiz & Pav.) Tul. essential oil against S. zeamais. In contact toxicity bioassay assessed treatments were 0 (control), 1.25, 2.5, 5.0, 10, 20, and 40 mL essential oil kg-1 grain and 0 (control), 25, 50, 75, 100, 125, 150, and 175 μL essential oil L-1 air in fumigant toxicity tests. The highest toxicity by contact activity was reached by concentrations higher than 10 mL essential oil kg-1 grain (100% mortality). The same treatments totally inhibit F1. The dose of 175 μL essential oil L-1 air showed a significant toxicity by fumigant activity causing 72.5% of dead insects. The other treatments did not surpass 5% mortality. In offspring effect (F1) bioassay, all treatments had an insect emergence significantly lower than the control but concentrations equal or higher than 10 mL essential oil kg-1 grain prevented the emergence of F1 during the 7 wk of bioassay. The residual effect of contact toxicity remained by 15 d. The treatments based on essential oil lead to a weight grain loss lower than control and germination was not affected. All assessed treatments showed repellent effect. The essential oil of L. sempervirens has promissory perspectives to maize weevil control.